Emerging techniques in molecular detection of circulating tumor cells. (March 2013) - Cho, William CS
Abstract : Circulating tumor cells (CTCs) are increasingly recognized for their potential utility in cancer diagnosis and prognosis. Emerging technologies in the past decade have allowed possible isolation and characterization of CTCs in the peripheral blood of cancer patients, including immunomagnetic technique coupled with immunofluorescence methodology, microfluidic platform, x-ray imaging technique and flow cytometry, filter-adapted FISH and miRNA microarray. Although there are still a number of challenges associated with the identification and molecular characterization of CTCs, the analysis of CTCs carries important prognostic and therapeutic implications for personalized cancer management.